The Effectiveness Of Soy Milk In Reducing Premenstrual Syndrome Symptoms In Adolescent Girls - Putri Amarela Wardana; Rifzul Maulina; Nila Widya Keswara (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2025)
Background : Premenstrual Syndrome (PMS) is a common condition affecting women of reproductive age, marked by a variety of physical, emotional, and behavioral symptoms that typically arise a few days before menstruation and diminish afterward. While the exact cause remains uncertain, hormonal fluctuations throughout the menstrual cycle are believed to be a key factor. Management strategies for PMS include both pharmacological and non-pharmacological approaches, one of which is soy milk consumption. Soy milk contains isoflavones, naturally occurring plant compounds that mimic estrogen activity and may help ease PMS symptoms. This study seeks to examine the impact of soy milk consumption on alleviating PMS symptoms in adolescent girls.. Methods : The research employed a pre-experimental method with a one-group pretest-posttest design, conducted from March 3 to 17, 2025. A total of 18 participants were selected using purposive sampling, and the sample size was determined using the Federer formula. Data were analyzed using a paired t-test with SPSS version 16.0. Results of the Paired T-test showed that the p-value ≤ α (0.05), namely 0.001 < 0.05, indicating that H1 is accepted and H0 is rejected. Conclusion : The data indicates that the administration of soy milk has an effect in reducing premenstrual syndrome symptoms in adolescent girls.